Urgensi Inovasi Pendidikan Islam: Menyatukan Dikotomi Pendidikan - Naif Naif (Akademika: Jurnal Keagamaan dan Pendidikan, 2016)
Education is one of the most important factors in the development efforts undertaken by a government. Because education is an effort to develop human potencies of learners in the form of physic, creativity and initiative for those potencies to be real and functioned for life. History records that a country having high attentions to education will develop higher compared to that of which does not. However, high attention from government is not merely enough; therefore practitioners and academics should strive to create relentless innovations in managing and developing education to improve the quality of education which aims at educating nations and establishing competitive and dignified human beings.